An empirical study of the impact of leadership, virtuousness and decision-making process on effectiveness of Indonesian private universities - Ahmad Nawaz; Edi Abdurachman; Idris Gautama; Asnan Furinto (STIE Binaniaga, 2020)
The purpose of this study is to investigate the relationship between servant / authentic leadership, organizational virtuousness, collegial / rational decision-making and organizational effectiveness of the departments at private universities. This study uses 97 faculty members’ data, collected from 78 departments in 17 private universities in Lembaga Layanan Pendidikan Tinggi (LLDikti) III. Structural Equation Modelling - Partial Least Square technique was used to determine statistical significance and path coefficients for the model. The findings indicate that servant leadership significantly affects organizational virtuousness, organizational virtuousness has a significant effect on both collegial / rational decision-making and organizational effectiveness, and organizational virtuousness has a significant effect on organizational effectiveness as well. This research reveals that servant leadership plays a substantial role in developing a virtuous culture, whereas authentic leadership has not contributed to encourage organizational virtuousness in private universities’ departments. Organizational virtuousness practices in departments result in more organizational effectiveness and enable them to exercise collegial / rational decision-making process for the allocation of resources. Moreover, the collegial / rational decision-making approach positively influences the effectiveness of the private universities’ departments. Keywords: Servant Leadership, Authentic Leadership, Organizational Virtuousness, Collegial / Rational Decision-Making, Organizational Effectiveness, Private Universities.